2007
DOI: 10.1590/s1677-55382007000300014
|View full text |Cite
|
Sign up to set email alerts
|

Mini-invasive collagen sling in the treatment of urinary incontinence due to sphincteric incompetence

Abstract: Pelvilace sling is safe and easy to introduce in both males and females if pelvic floor anatomy is normal. Although immediate results were promising in neuropathic incontinence, the results seem to deteriorate to unacceptable low level already during the first year. In exstrophy patients the results are generally poor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
(7 reference statements)
0
3
0
Order By: Relevance
“…We are aware of only one published report of the effectiveness of Pelvilace, a case series of patients (male and female) with neuropathic urinary incontinence. Improvement was noted in 9 of 11 at 12 months, but none was completely dry [3].…”
Section: Introductionmentioning
confidence: 94%
“…We are aware of only one published report of the effectiveness of Pelvilace, a case series of patients (male and female) with neuropathic urinary incontinence. Improvement was noted in 9 of 11 at 12 months, but none was completely dry [3].…”
Section: Introductionmentioning
confidence: 94%
“…Data on the outcome of the mini-sling procedure is still sparse. Tasinen et al (8) have reported very poor results one year after surgery using a mini-invasive collagen sling to treat neurogenic urinary incontinence. Neuman has reported a failure rate of 7% in a study of 100 women who underwent TVT-SECUR insertion (9) in 13 hospitals.…”
Section: Neurourology Neurourologymentioning
confidence: 99%
“…Synthetic meshes can also be used for urinary sphincter incontinence. Taskinen compared mesh versus ECM from PD and followed up cases at 1, 6 and 12 months after surgery 10 . Although the surgical technique is easy, it involves high risks when working on normal pelvic anatomy and the results in neuropathic incontinence are promising, the 12-month postoperative data collected were not satisfying at all.…”
Section: Introductionmentioning
confidence: 99%